Tissue engineered hydrogels supporting 3D neural networks - Aregueta-Robles,UA; Martens,PJ; Poole-Warren,LA; Green,RA (Acta Biomaterialia, 2019)
Promoting nerve regeneration requires engineering cellular carriers to physically and biochemically support neuronal growth into a long lasting functional tissue. This study systematically evaluated the capacity of a biosynthetic poly(vinyl alcohol) (PVA) hydrogel to support growth and differentiation of co-encapsulated neurons and glia. A significant challenge is to understand the role of the dynamic degradable hydrogel mechanical properties on expression of relevant cellular morphologies and function. It was hypothesised that a carrier with mechanical properties akin to neural tissue will provide glia with conditions to thrive, and that glia in turn will support neuronal survival and development. PVA co-polymerised with biological macromolecules sericin and gelatin (PVA-SG) and with tailored nerve tissue-like mechanical properties were used to encapsulate Schwann cells (SCs) alone and subsequently a co-culture of SCs and neural-like PC12s. SCs were encapsulated within two PVA-SG gel variants with initial compressive moduli of 16kPa and 2kPa, spanning a range of reported mechanical properties for neural tissues. Both hydrogels were shown to support cell viability and expression of extracellular matrix proteins, however, SCs grown within the PVA-SG with a higher initial modulus were observed to present with greater physiologically relevant morphologies and increased expression of extracellular matrix proteins. The higher modulus PVA-SG was subsequently shown to support development of neuronal networks when SCs were co-encapsulated with PC12s. The lower modulus hydrogel was unable to support effective development of neural networks. This study demonstrates the critical link between hydrogel properties and glial cell phenotype on development of functional neural tissues. STATEMENT OF SIGNIFICANCE: Hydrogels as platforms for tissue regeneration must provide encapsulated cellular progenitors with physical and biochemical cues for initial survival and to support ongoin